2013
DOI: 10.1111/epi.12456
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hamartoma: Is the epileptogenic zone always hypothalamic? Arguments for independent (third stage) secondary epileptogenesis

Abstract: SUMMARYGelastic seizures associated with hypothalamic hamartomas (HHs) are a clinicoradiologic syndrome presenting with a variety of symptoms, including pharmacoresistant epilepsy with multiple seizure types, electroencephalography (EEG) abnormalities, precocious puberty, behavioral disturbances, and progressive cognitive deterioration. Surgery in adults provides seizure freedom in only one third of patients. The poor results of epilepsy surgery could be explained by an extrahypothalamic epileptogenic zone. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 18 publications
0
35
0
3
Order By: Relevance
“…The latter hypothesis, consisting of a kindling model of epileptogenesis, introduces the variable “time” in the prognosis of the syndrome after surgery. Scholly et al . recently highlighted that successful surgery is often achievable for children with HH and should be performed as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The latter hypothesis, consisting of a kindling model of epileptogenesis, introduces the variable “time” in the prognosis of the syndrome after surgery. Scholly et al . recently highlighted that successful surgery is often achievable for children with HH and should be performed as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…[28] It is assumed that seizure-induced neuronal death and associated fibre degeneration leads to mossy fibre sprouting and synaptic reorganization thus forming recurrent excitatory circuits. This is regarded as the underlying pathological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been observed that additional seizure types often appeared with a clear delay following the start of gelastic seizures during the clinical course . We also observed this phenomenon in the Strasbourg‐Kork series of 15 patients explored for an HH . All patients experienced gelastic seizures, and they also presented one or several other seizure types.…”
Section: Human Data Arguing For Secondary Epileptogenesis In Hhmentioning
confidence: 99%
“…These cases illustrate the existence of an independent, extrahypothalamic secondary epileptogenic zone, without running down after the removal of the presumably primary epileptogenic lesion. Thus they argue for existence of a third, independent stage of secondary epileptogenesis in humans …”
Section: Human Data Arguing For Secondary Epileptogenesis In Hhmentioning
confidence: 99%